An exploration of patient-provider dynamics and childbirth experiences in rural and urban Peru: a qualitative study - Brianna Vargas; Paola Louzado-Feliciano; Nicole Santos; Shannon Fuller; Sopiko Jimsheleishvili; Ángela Quiñones; Holly H. Martin (BMC, 2021)
Abstract Background Between 2006 and 2013, Peru implemented national programs which drastically decreased rates of maternal and neonatal mortality. However, since 2013, maternal and neonatal mortality in Peru have increased. Additionally, discrimination, abuse, and violence against women persists globally and impacts birthing experiences and mental health. This qualitative study sought to better understand the attitudes and beliefs regarding childbirth among women and providers in Southern Peru. This study also explores how these beliefs influence utilization of skilled care, patient-provider dynamics, and childbirth experiences and identifies factors that impact providers' provision of care. Methods Thirty semi-structured interviews were conducted with 15 participants from rural Colca Canyon and 15 participants from urban Arequipa between April and May 2018. In each region, 10 women who had experienced recent births and five providers were interviewed. Provider participants predominantly identified as female and were mostly midwives. All interviews were conducted, transcribed, and coded in Spanish. A framework analysis was followed, and data were charted into two separate thematic frameworks using contextual and evaluative categories of conceptualization of childbirth. Results All recent births discussed were facility-based births. Four domains emerged: women's current birth experiences, provision of childbirth care, beliefs about childbirth among women and providers, and future health-seeking behavior. Findings suggest that women's feelings of helplessness and frustration were exacerbated by their unmet desire for respectful maternity care and patient advocacy or companionship. Providers attributed strain to perceived patient characteristics and insufficient support, including resources and staff. Conclusions Our findings suggest current childbirth experiences placed strain on the patient-provider dynamic and influenced women's attitudes and beliefs about future experiences. Currently, the technical quality of safe childbirth is the main driver of skilled birth attendance and facility-based births for women regardless of negative experiences. However, lack of respectful maternity care has been shown to have major long-term implications for women and subsequently, their children. This is one of the first studies to describe the nuances of patient-provider relationships and women's childbirth experiences in rural and urban Peru.